Suppression of reward-induced dopamine release in the nucleus accumbens in animal models of depression: Differential responses to drug treatment. (22nd May 2017) - Minami, Saki; Satoyoshi, Hiroshi; Ide, Soichiro; Inoue, Takeshi; Yoshioka, Mitsuhiro; Minami, Masabumi
Highlights: Reward-induced dopamine release was suppressed by chronic mild stress in rats. Escitalopram reversed chronic mild stress-induced suppression of dopamine release. Dopamine release may be a useful indicator of therapeutic efficacy in depression. Maternal separation diminished the effect of escitalopram in stressed rats. Potential animal models for treatment-sensitive and treatment-resistant depression. Abstract: Anhedonia, the loss of interest or pleasure in previously enjoyable activities, is a core symptom of major depressive disorder, suggesting that the brain reward system may be dysfunctional in this condition. Neurochemical changes in the mesolimbic dopamine (DA) system are not fully understood in animal models of depression. We investigated reward (30% sucrose intake)-induced DA release in the nucleus accumbens (NAc) and the effect of chronic treatment with the antidepressant escitalopram (5 mg/kg, intraperitoneally twice daily for 3 weeks) in two animal models of depression. Exposure to chronic mild stress (CMS) during adulthood completely suppressed reward-induced intra-NAc DA release; however, this effect was reversed by chronic treatment with escitalopram. Our findings suggest that reward-induced intra-NAc DA release may be an indicator of depression severity and therapeutic efficacy. Exposure to neonatal maternal separation (MS) and CMS in adulthood completely suppressed reward-induced intra-NAc DA release. Chronic treatment with escitalopram did not restore reward-induced DA release in these animals, suggesting that this paradigm may serve as an animal model for treatment-resistant depression. Further study of the mesolimbic dopaminergic system in these animal models of depression may clarify the neural mechanisms underlying depression and treatment resistance.